Contaminação de superfícies em enfermarias de pacientes com infecções por Staphylococcus aureus no Hospital de Clínicas na Universidade Federal de Uberlândia - Carvalho, Karinne Spirandelli (2005)
Hospital environment represents a secondary reservoir of pathogens as Staphylococcus aureus, including MRSA, mainly the surfaces that can be touched and cotaminated by healthcare personnel hands. This study was achieved in the Uberlândia University Hospital, MG - Brazil, between January and August 2004. The objective of this study was to assess qualitative and quantitatively the contamination of surfaces touched by hands (over-bed tables, room door handles and side rails) and floors by S. aureus (MRSA and MSSA) in rooms from patients with infection by this microorganism. Fifty two patients were investigated, including 26 with infection (cases) and 26 controls. The surface was sampled during bedmaking by using the stamp method with sterile adhesive tapes (6 cm2) which was placed on Egg Yolk Salt Agar. S. aureus was identified by Gram staining and the coagulase test. S. aureus was detected in 50% of rooms without differences between the two groups (46,2% in the infected patients versus 53,8% in the controls). The difference in the density of S. aureus contamination was also not significant in both groups but the floor contamination was 5 fold higher than in other sites. This results suggest extensive contamination of S. aureus in the hospital but the density was less than 1 CFU/cm2. The numbers of S. aureus on the floor and the other sites did not correlated with those in the air in the room. Despite of more patients were infected and / or colonized by MRSA than MSSA isolates the latter were more frequent (65,7% versus 34,3%) in the environmental sites. In conclusion, we found an extensive environmental contamination with S. aureus in a hospital caring for many infected and colonized patients. Actually this is not generally regarded as a major source of S. aureus infection but is widely recognized that further investigations in the clinical significance of the hospital environmental contamination and of more effective cleaning methods are necessary.